Examining Social Media Public Sentiment: Youtube Response to 2024 Indonesian Presidential Debate - Syam, Andi Armayudi; Afdal, Andi Ahmad Malikul (Kybernology : Journal of Government Studies, 2024)
This research aims to analyze public sentiment on YouTube social media regarding the 2024 Indonesian presidential candidate debate. The method used is sentiment analysis using big data analysis with the help of Nvivo. The data used are public comments contained in the 2024 Indonesian presidential candidate debate video on YouTube. The research results show that the majority of public sentiment towards the 2024 Indonesian presidential candidate debate is positive. However, there are also several comments that are negative and neutral. The theme most discussed by the public in the 2024 Indonesian presidential candidate debate is "Prabowo". This shows the dominance of public attention towards Prabowo. Apart from that, other words that are quite dominant are "people" and "Anies", which reflects the competition between the Prabowo camp and the Anies camp in the 2024 presidential election. Apart from that, the results of the wordcloud analysis highlight crucial issues that are the main topic of discussion. post-debate society, such as corruption, political promises, and the law. This shows that public discourse after the presidential candidate debate was greatly influenced by issues that influence social and political life in Indonesia.